ANALYSIS OF AN H6 INVERTER FOR TRANSFORMERLESS THREE-PHASE PV SYSTEMS (International Journal of Engineering Management Science, 2022)
Eliminating the leakage current is one of the most important issues for transformer less three phase photovoltaic (PV) systems. In this paper, the leakage current elimination of a three-phase four-leg PV inverter is investigated. With the common mode loop model established, the generation mechanism of the leakage current is clearly identified. Different typical carrier-based modulation methods and their corresponding common mode voltages are discussed. A new modulation strategy with Boolean logic function is proposed to achieve the constant common mode voltage for the leakage current reduction. Finally the different modulation methods are implemented and testedonthe TMS320F28335DSP +XC3S400FPGAdigital control platform. The experimental results. The transformer less inverter topologies Solar cells produce direct current electricity from sun light which can be used to power equipment or to recharge a battery. The first practical application of photovoltaic was to power orbiting satellites and other spacecraft, but today the majority of photovoltaic modules are used for grid connected power generation. In this case an inverter is required to convert the DC to AC. There is a smaller market for off-grid power for remote have superior efficiency thanks to saving transformer but there semiconductor devices still hard switching stated present. A family of ZCT transformer less inverter with sinusoidal PWM modulation is deduced by using fuzzy logic controller.